COVID-19 vaccine registry for pregnant women: policy to control complications of vaccination in pregnant women in 2021–2022 - Farkhondeh Asadi; Roya Shakiba; Reza Rabiei; Hassan Emami; Azam Sabahi (BMC Pregnancy and Childbirth, 2023)
Abstract Background Data management related to COVID-19 vaccination in pregnant women is vital to improve the treatment process and to establish preventive programs. Implementing a registry to manage data is an essential part of this process. This study aims to design a national model of the COVID-19 vaccination registry for pregnant women in Iran. Methods The present study is an applied descriptive study conducted in 2021 and 2022 in two stages. In the first stage, the coordinates of the National Registry of COVID-19 vaccination of pregnant women from related references and articles, as well as the comparative study of the National Registry of COVID-19 vaccination of pregnant women in the United States, Canada, and the United Kingdom was done. In the second stage, the preliminary model was designed. The model was validated using the Delphi technique and questionnaire tools and analyzing the data. Results The presented national COVID-19 vaccination registry model of pregnant women’s main components consist of objectives, data sources, structure, minimum data set, standards, and registry processes, all of which received 100% expert consensus. Conclusion The vaccination registry of pregnant women has a major role in managing COVID-19 vaccination data of pregnant women and can be one of the Ministry of Health and Medical Education priorities.